An insight to tympanic membrane perforation pressure through morphometry: A cadaver study - Talas, Derya Ümit (Diving Hyperb Med, 2021)
INTRODUCTION: A cadaveric experimental investigation aimed to show the rupture pressure of the tympanic membrane (TM) for otologists to evaluate its tensile strength. METHODS: Twenty adult ears in 10 fresh frozen whole cadaveric heads (four males, six females) mean age 72.8 (SD 13.8) years (range 40–86) were studied. The tensile strength of the TM was evaluated with bursting pressure of the membrane. The dimensions of the membranes and perforations were measured with digital imaging software. RESULTS: The mean bursting pressure of the TM was 97.71 (SD 36.20) kPa. The mean area, vertical and horizontal diameters of the TM were 57.46 (16.23) mm(2), 9.54 (1.27) mm, 7.99 (1.08) mm respectively. The mean area, length and width of the perforations were 0.55 (0.25) mm(2), 1.37 (0.50) mm, and 0.52 (0.22) mm, respectively. Comparisons of TM dimension, bursting pressure, and perforation size by laterality and gender showed no significant differences. The bursting pressure did not correlate (positively or negatively) with the TM or perforation sizes. CONCLUSIONS: The TM can rupture during activities such as freediving or scuba diving, potentially leading to serious problems including brain injuries. Studying such events via cadaveric studies and data from case studies is of fundamental importance. The minimum experimental bursting pressures might better be taken into consideration rather than average values as the danger threshold for prevention of TM damage (and complications thereof) by barotrauma.